Toxic and genotoxic effects of hexavalent chromium in environment and its bioremediation strategies. (2nd January 2016) - Mishra, Sandhya; Bharagava, Ram Naresh
Abstract: Chromium is one of the major inorganic environmental pollutants, which is added in the environment through various natural and anthropogenic activities and exists mainly in two forms: Cr(III) and Cr(VI). Cr(VI) is considered to be more toxic than Cr(III) due to its high solubility and mobility. It is a well-reported occupational carcinogen associated with lung, nasal, and sinus cancers. Thus, this review article provides the detailed information on the occurrence, sources of chromium contamination in the environment and their toxicological effects in human, animal, plants as well as in microorganisms, and bioremediation strategies to minimize the toxic effects.